Peran Dukungan Keluarga dalam Pengendalian Kadar Glukosa Darah pada Lansia Diabetes Melitus - Matindas, Felicia; Fani, Rif'atul; Maharani, Ananda Sagita (Pustaka Galeri Mandiri, 2026)
Diabetes mellitus is a chronic disease with a rapidly increasing prevalence among older adults. Poor glycemic control in the elderly increases the risk of complications, reduces quality of life, and leads to greater health care utilization. Beyond pharmacological treatment, family support is an important non-pharmacological factor that may influence diabetes self-management and blood glucose control, particularly in primary health care settings. This study aimed to examine the role of family support in controlling blood glucose levels among older adults with diabetes mellitus. A quasi-experimental study with a pre-test and post-test control group design was conducted among 40 older adults with diabetes mellitus in the working area of Tadoy Primary Health Care Center, North Sulawesi, Indonesia. Participants were assigned to an intervention group (n = 20) receiving structured family support in addition to routine care, or a control group (n = 20) receiving routine care only. Blood glucose levels were measured before and after the intervention and analyzed using paired and independent t-tests. The intervention group showed a significant reduction in blood glucose levels (p = 0.000), whereas the control group showed no significant change (p = 0.087). The reduction was significantly greater in the intervention group than in the control group (p = 0.000). Family support significantly improves blood glucose control among older adults with diabetes mellitus. Integrating family-based approaches into primary health care is recommended to enhance diabetes management in elderly populations.